Olive oil tourism: state of the art - José Manuel Hernández-Mogollón; Elide Di-Clemente; José Antonio Folgado-Fernández; Ana María Campón-Cerro (Tourism and Hospitality Management, 2019)
Purpose – Oleotourism has recently caught the attention of researchers in the field of tourism marketing and management. Contributions on this subject begin to outline a significant research body that can be properly identified and organised through a detailed literature review in order to figure out state of the art of the subject and the future research lines. Design – After a thorough literature search, the documents obtained have been categorised according to the study perspective adopted: the demand, the supply and the potential for tourism development. Methodology – Online search and content analysis have been the methodology adopted for this work. The literature review has been developed using the databases of WOS and Scopus as a main reference. The research has been carried out firstly using a search process by keywords and secondly a cross-reference check with the bibliographies of the articles obtained. Approach – The study opts for a descriptive and analytical approach. Findings – An incipient, but significant theoretical body has been identified about the oleotourism that defines a new research line. Oleotourism resulted to be a qualifying tourism practice which should be further developed from both a theoretical and practical perspective. Originality of the research – This work is one of the first attempts to organise the literature on olive-oil tourism, identify the aspects of this tourism practice that are awakening greater interest among the scientific community, and outline new paths to be followed in the future.